Magnetic Marketing Success Factors and Their Impact on Purchasing Decision Making Exploration Research in a Sample of Private Banks in Baghdad - Arif Braism, Maha; Dawood Salman, Adil; Mohammed Ibrahim, Ahmed (International Journal of Supply Chain Management, 2019)
The research examines the impact relationship of magnetic marketing success factors (market, message and media"means of advertising") in making a purchase decision. The problem of the research was represented in number of questions, the aim of the answer was to find out the extent to which the sample was (private banks in Baghdad) adopted the factors of the success of the magnetic marketing and their impact on making a purchase decision .The importance of the research lies in the importance of the factors of the success of magnetic marketing in communication with existing customers and thus the exchange with them and seek to attract potential customers. The aim of the research to raise the interest of these organizations to the variables of the study of its importance in ensuring the survival and sustainability. The questionnaire was used as a tool for collecting the data that was distributed to the sample of the research which included (63) respondents in a sample of private banks in Baghdad (Baghdad, United Investment, Gulf Business and International Development). A number of statistical methods have been used to test the hypothesis of research through the adoption of the statistical program (SPSS23 ) found a number of conclusions, the most important of which was the significant effect of the success factors of magnetic marketing in making the purchase decision, while the most important recommendations is the need to adopt the management of the bank a mix of advertising means and not the adoption of the Internet and e-mail as a single means of promotion and exchange if they want to apply magnetic marketing success factors.